2018
DOI: 10.1080/14764172.2017.1418514
|View full text |Cite
|
Sign up to set email alerts
|

Picosecond alexandrite laser is superior to Q-switched Nd:YAG laser in treatment of minocycline-induced hyperpigmentation: A case study and review of the literature

Abstract: Minocycline is a commonly prescribed tetracycline antibiotic used for the treatment of a number of dermatological conditions including acne and rosacea. Long-term adverse effects of minocycline include cutaneous hyperpigmentation. Various treatment options have been suggested for the treatment of minocycline pigmentation. We report a case of a patient on long-term low-dose minocycline for the treatment of rosacea with type III minocycline hyperpigmentation. A comparison was made between Q-Switch Nd:YAG and pic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…Although these reports cast an optimistic outlook on the expanded use of picosecond lasers, further evidence is required in order to draw reliable conclusions. That being said, it is worthwhile noting that some traditionally difficult conditions to treat, such as minocycline-induced hyperpigmentation and chronic venous stasis hyperpigmentation have shown promising response and the use of picosecond laser in these settings should be considered an alternative treatment option when other modalities have proven unsatisfactory [30][31][32][33][34][35][36][37][38][39][41][42][43][44][45]94].…”
Section: Other Non-melasma Pigmented Conditionsmentioning
confidence: 99%
“…Although these reports cast an optimistic outlook on the expanded use of picosecond lasers, further evidence is required in order to draw reliable conclusions. That being said, it is worthwhile noting that some traditionally difficult conditions to treat, such as minocycline-induced hyperpigmentation and chronic venous stasis hyperpigmentation have shown promising response and the use of picosecond laser in these settings should be considered an alternative treatment option when other modalities have proven unsatisfactory [30][31][32][33][34][35][36][37][38][39][41][42][43][44][45]94].…”
Section: Other Non-melasma Pigmented Conditionsmentioning
confidence: 99%
“…After three treatments with a 755-nm alexandrite picosecond laser and a 2.5-year follow-up, pigmentation completely disappeared, which was verified by dermoscopy. Barrett et al 14 reported the case of an 81-year-old white woman with PIH caused by oral minocycline for rosacea. Five treatments with a 1064-nm nanosecond laser and 532nm Q-switched laser produced poor results, but four subsequent treatments with a 755-nm alexandrite picosecond laser produced complete disappearance of the pigmentation.…”
Section: Discussionmentioning
confidence: 99%
“…In this meta‐analysis from Asian patients treated with a PS laser, the proportions of patients achieving excellent outcomes were higher for nevus of Ota and solar lentigines, consistent with the literature. On the other hand, the treatment of other nonmelasma pigmentary lesions with PS laser was satisfactory 44‐58 . Based on a systematic review, the level of evidence for the use of the PS laser for other pigmentary lesions was 4, 15 highlighting the need for high‐quality research on the subject.…”
Section: Discussionmentioning
confidence: 99%